2017
DOI: 10.1007/s12035-017-0627-y
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Hypothyroxinemia Imprints a Switch in the Capacity of Astrocytes and Microglial Cells of the Offspring to React in Inflammation

Abstract: Hypothyroxinemia (Hpx) is a highly frequent condition characterized by low thyroxine (T) and normal 3,3',5'-triiodothyronine (T) and thyroid stimulating hormone (TSH) levels in the blood. Gestational Hpx is closely related to cognitive impairment in the human offspring. In animal models gestational Hpx causes impairment at glutamatergic synapsis, spatial learning, and the susceptibility to suffer strong autoimmune diseases like experimental autoimmune encephalomyelitis (EAE). However, the mechanisms underlying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 68 publications
1
16
0
Order By: Relevance
“…Maternal hypothyroxinemia during the first half of gestation has been associated with permanent and irreversible neurological alterations in the embryo and the foetus [ 44 ]. Experimental animal studies have contributed to a better characterization of cerebral areas affected by inadequate availability of fT4 ( Table 1 ) [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…Maternal hypothyroxinemia during the first half of gestation has been associated with permanent and irreversible neurological alterations in the embryo and the foetus [ 44 ]. Experimental animal studies have contributed to a better characterization of cerebral areas affected by inadequate availability of fT4 ( Table 1 ) [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…Gestational HTX was induced in pregnant mice according to previous reports ( 52 55 ). Six- to eight-week-old C57BL/6 mice were mated in a proportion of 2 females and 1 male.…”
Section: Methodsmentioning
confidence: 99%
“…An interplay between thyroid hormone action and peripheral immune cells has been established with evidence of actions in both the innate and adaptive immune responses (Montesinos and Pellizas, 2019). Earlier work reported that microglia express the a1 and b1 isoforms of nuclear thyroid hormone receptors (Lima et al, 2001) and, under conditions of developmental hypothyroxinemia, show a decrease in cellprocess complexity Lima et al, 2001) and diminished response to a LPS challenge (Opazo et al, 2018). Thus, if exposure results in a direct effect upon microglia or if the effect is secondary to a shift in thyroid hormone or a change in BBB transporters, there remains an effect upon these critical cells of the brain even if only localized to those microglia in contact with the vascular wall.…”
Section: Discussionmentioning
confidence: 99%